A influência da agenda mercosulina na criação do Conselho de Defesa Sul-Americano - Lotério, Bruno [UNESP] (2014)
In recent years there has been a shift in behavior among South American countries, whereas 30 years ago the tone of foreign policy was dominated by mistrust, in our times the countries deepen and increase the agendas of cooperation in defense and security. In such context, arises the Union of South American Nations (Unasul), and as part of it, the South American Defense Council (CDS), responsible for the organization and cooperation in defense and security in South America, in opposition to the treatment in the hemispheric scope pursued until then. The various plans and perspectives that South Americans countries have created an agenda conflict within the CDS, from the Bolivarian agenda driven by Venezuelan President Hugo Chávez, to the agenda of Mercosul countries, called mercosulina, the subject of this research.